On the Interest Subjects of Independent Innovation in the Manufacturing Industry in Northeast China (Global Journal of Management and Business Research, 2014)
This paper identifies the interest subjects for the innovation system of manufacturing industries in northeast China, including manufacturing enterprises, governments, industry chain users, universities and research institutes, financial institutions, and intermediary organs. Therefore, analyzing the interest subjects promoting independent innovation activities in manufacturing industries in northeast China is an effective means to choose elements of industrial innovation impetus.
Keywords: northeast region; manufacturing industry; independent innovation; interest subjects